KS01.6.A Comparative analysis of the immune compartment in human glioblastoma and IDH-mutant WHO grade 4 astrocytoma reveals profound differences in microglia phenotypes. (9th September 2021) - Sankowski, R; Friedrich, M; Bunse, L; Heiland, H H; Platten, M; Prinz, M
Abstract: BACKGROUND: Glioblastoma (GBM) are the most common primary brain tumors. If untreated the average survival is around 12–18 months. Unfortunately, despite extensive research efforts, the therapeutic options remain limited. One major aspect complicating therapeutic development is an immunosuppressive tumor microenvironment. Isocitrate dehydrogenase (IDH)-mutant, WHO grade 4 astrocytomas appear histologically indistinguishable from GBM, but show significantly longer survival times. IDH mutations lead to changes in the tumor microenvironment with accrual of the neometabolite R-2-hydroxyglutarate. Previous studies on bulk transcriptomes have shown differences in the immune compartment of both tumor entities that were linked to the differences in clinical behavior. MATERIAL AND METHODS: We have conducted high-dimensional comparative analyses of the myeloid compartment in surgically resected human GBM and IDH-mutant WHO grade 4 astrocytomas using single-cell RNA-Sequencing and immunohistochemistry. Histologically normal brain regions from epilepsy patients were used as controls. For analysis, whole-cell suspensions were prepared from freshly resected tumors or controls. Fluorescence activated cell sorting was used for myeloid cell enrichment. Samples were processed using the high-sensitivity single-cell RNA sequencing protocol CEL-Seq2. Seurat and StemID2 algorithms were used for clustering, differential gene expression and pseudotime analysis. Protein validation was achieved using immunohistochemistry. RESULTS: We identified profound transcriptional changes of glioma-associated microglia in GBM with respect to control brain samples. Namely, we observed a global upregulation of major histocompatibility complex associated genes in GBM across all clusters. Additionally, we identified distinct myeloid subsets with phagocytic, hypoxia-associated and chemotactic transcriptomic signatures. Pseudotime analysis finely resolved transitional cell states. These changes were dramatically attenuated in IDH-mutant WHO grade 4 astrocytomas. The myeloid cells in these tumors resembled homeostatic microglia and showed an increased expression of cytokine and chemokine genes. CONCLUSION: Here, we present a high-dimensional transcriptomic atlas of the myeloid compartment in human GBM and IDH-mutant WHO grade 4 astrocytomas. The identified differences point towards targeted therapeutic options via the modulation of the tumor microenvironment.